Front Cover: An Integrated Continuous‐Flow Synthesis of a Key Oxazolidine Intermediate to Noroxymorphone from Naturally Occurring Opioids (Eur. J. Org. Chem. 44/2017). Issue 44 (9th November 2017) - Mata, Alejandro; Cantillo, David; Kappe, C. Oliver
Abstract : The Front Cover shows the synthetic sequence towards noroxymorphone, a key intermediate in the preparation of important opioid antagonists such as naltrexone or naloxone. The process starts from oripavine, a naturally occurring compound in the poppy plant extract, and consists of a sequential oxidation with hydrogen peroxide to give the 14‐hydroxymorphinone derivative followed by hydrogenation and palladium‐catalyzed aerobic N ‐demethylation. All synthetic steps have been integrated under continuous flow conditions. More information can be found in theFull Paper by A. Mata, D. Cantillo, and C. O. Kappe. See also theFull Paper by B. Gutmann, C. O. Kappe et al.